DESAIN DAN PEMBANGUNAN MULTIMEDIA INTERAKTIF PEMBELAJARAN FISIKA MATERI CAHAYA DI SMP - Yulia '; Muhammad Nasir; M.Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The aimed of this research is to design and build phisics learning multimedia interactive for light in Junior High School. This research was conducted at Riau University in April to June 2016. This type of research was Research and Development (R&D) and designed of multimedia interactive used ADDIE (Analyse, Design, Development, Implementation, and Evaluation) instructional design model. It using historyboard, flowchart and storyboard and as resultor of designed. It was use lectora inspire softwere. Based on data validity by 7 expert and 9 expert user that multimedia interactive was valid based on all aspect which was design aspect in high categories for expert and very high categories for expert user. Pedagogy aspect in high categories for expert and very high categories for expert user. Content aspect in high categories for for expert and very high categories for expert user and usability aspect in high categories for for expert and very high categories for expert user. Validator suggestion has been did to repair and complete multimedia interactive based on suggestions validator. So, multimedia interactive was valid with got score 4,09 for expert and 4,37 for expert user.Key Words: Design, development, multimedia interactive, validity, light, lectora inspire